2D Raman spectroscopy study of dolomite and cyanobacterial extracellular polymeric substances from Khor Al‐Adaid sabkha (Qatar). (29th August 2013) - Paulo, Carlos; Dittrich, Maria
<x xml:space="preserve">Abstract</x> Dolomite precipitation, limited at low temperature, appears to be impacted by microbial extracellular polymeric substances (EPS). The presence of dolomites has been reported in the extreme environments of Arabian Gulf sabkhas. Many of these sites are characterized by extensive growth of cyanobacterial mats that are recognized as key producers of EPS. However, no information has been gathered on the cyanobacterial EPS involvement in dolomite precipitation. The objective of this study was to obtain in situ information on the spatial distribution of cyanobacterial EPS and dolomite in Khor Al‐Adaid sabkha (Qatar) sediments by chemical mapping. For this purpose, in situ 2D Raman spectroscopy and atomic force microscopy were applied. Additionally, samples were analyzed with scanning electron microscopy and X‐ray diffraction. Raman fingerprints of dolomite (300, 725, and 1098 cm−1), cyanobacteria, and their EPS (1000, 1130, 1148, and 1508 cm−1) were observed widely distributed in the top 2 cm of the sabkhas sediments. 2D chemical imaging of sediment layers characterized minerals and organic matter of microbial origins at high spatial resolution. Raman mapping indicated small dolomite clusters (<2 µm) embedded in a dense cyanobacterial EPS matrix. The spatial distribution showed that small dolomite clusters are closely associated with cyanobacterial EPS and organic carbon. Our results prove that cyanobacterial molecules are closely related to dolomite in the sabkhas sediments. This study demonstrated that Raman mapping is a robust and sensitive technique for acquisition of in situ information on cell–mineral interactions. Copyright © 2013 John Wiley & Sons, Ltd.